(untitled) (Bangladesh Journal of Medical Science, 2015)
Background: Vaginal discharge and associated vaginal symptoms is very common amongst women of South East Asia, hence it is necessary to make accurate diagnosis and also for appropriate treatment by identifying the causative microorganisms. Objectives: To analyze the socio-demographic and microbiological profile of vaginal discharge. Methodology: This is a prospective, non-randomized study performed in one hundred and ninety three patients attending in Department of Obstetrics and Gynecology in Kathmandu University Hospital, Dhulikhel, Nepal. The patients with vaginal discharge and age of ?16 years included. Vaginal discharge was taken from the posterior and lateral fornices. The swab was cultured on blood, chocolate and Mac Conkeys agar and incubated at 37°C for 24-48 hours. Fungus when isolated was subcultured onto Sabouraud dextrose agar. The data were analyzed using the SPSS 11.5 software. Result: The frequency of vaginal discharge was 1.67%. Most of the patients fell within 16-25 years. 50.3% patients were illiterate whereas only 3.1% was having master degree. 50.3% patients were having class V socioeconomic status where as only 2.6% had class I status. Housewife accounted for 67.9% whereas other occupation (petty business) accounted for only 5.2%. Most of the patients with vaginal discharge were from Newar and Tamang ethnic group. Bacterial vaginosis was isolated in 36.3% and normal flora accounted for 20.7%. Conclusion: There is still lack of awareness about the vaginal discharge be it abnormal discharge or physiological leucorrhea and related problems. So, it is worthwhile to create public awareness and also to find out the socio-demographic factors affecting the pattern of microbiological flora variation in vaginal discharge, as it gives us the clue regarding the use of appropriate antimicrobial therapy and the changes that can be made to the quality of life of the women. Bangladesh Journal of Medical Science Vol.14(4) 2015 p.323-326